2008
DOI: 10.1254/jphs.fm0070073
|View full text |Cite
|
Sign up to set email alerts
|

Basic and Clinical Aspects of Non-neuronal Acetylcholine: Overview of Non-neuronal Cholinergic Systems and Their Biological Significance

Abstract: Abstract. Acetylcholine (ACh) is a phylogenetically ancient molecule involved in cell-to-cell signaling in almost all life-forms on earth. Cholinergic components, including ACh, choline acetyltransferase, acetylcholinesterase, and muscarinic and nicotinic ACh receptors (mAChRs and nAChRs, respectively) have been identified in numerous non-neuronal cells and tissues, including keratinocytes, cancer cells, immune cells, urinary bladder, airway epithelial cells, vascular endothelial cells, and reproductive organs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
122
0
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 73 publications
5
122
0
3
Order By: Relevance
“…The subunits have been cloned from neuron-like cells or cDNA libraries obtained from vertebrate brain, but it has recently been shown that some of them are expressed by non-neuronal cell types throughout the body and have various functions. However, the nAChRs expressed in non-neuronal tissues are beyond the scope of this review and interested readers are referred elsewhere [17][18][19][20][21].…”
Section: Structure Of Thenachrmentioning
confidence: 99%
“…The subunits have been cloned from neuron-like cells or cDNA libraries obtained from vertebrate brain, but it has recently been shown that some of them are expressed by non-neuronal cell types throughout the body and have various functions. However, the nAChRs expressed in non-neuronal tissues are beyond the scope of this review and interested readers are referred elsewhere [17][18][19][20][21].…”
Section: Structure Of Thenachrmentioning
confidence: 99%
“…In mammals, Ach induces vascular smooth muscle relaxation by activation of muscarinic receptors expressed in endothelial cells (Furchgott and Zawadzki, 1980). Molecular approach has demonstrated the presence of muscarinic receptors type 1-3 in arterial vessels (See review, Kawashima and Fujii, 2008). Furthermore, pharmacological studies support the presence of functional muscarinic receptors type 1 and 3 (Norel et al, 1996).…”
Section: Vascular Response To Acetylcholinementioning
confidence: 99%
“…Since there is increasing evidence of the relevant role of nonneuronal nAChRs ligands in nicotinic function and modulation (Miwa et al, 1999;Grando, 2008;Kawashima & Fujii, 2008), we tested and confirmed the expression of lynx1, the endogenous modulator of a7 receptor, in the bovine retina and RPE. We also showed the expression of other members of the Ly-6/neurotoxin gene family in rat retina: lynx1, RGD1308195, and SLURP-1.…”
Section: Discussionmentioning
confidence: 98%